Late duodenal leaks following pancreas transplantation with bladder drainage treated without conversion - Nicoluzzi, João Eduardo; Silveira, Fábio; Marmanillo, Carlos (Brazilian Journal of Transplantation, 2007)
Improvements brought by bladder drainage in early postoperative mortality came at the price of late morbidity. Urinary leaks related to duodenal stump, although not very frequent, are still a matter of discussion on the best treatment. Many surgeons support enteric conversion as the best choice. Here, we report two cases of late duodenal leaks successfully managed without enteric conversion.